2005
DOI: 10.2466/pms.100.3.865-873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Display and Speed of Display Movement on Reading Chinese Text Presented on a Small Screen

Abstract: Automatic dynamic displays, e.g., scrolling displays, are frequently used to present text information on small screens. This study examined the effects of three dynamic displays [leading, scrolling, and rapid serial visual presentation (RSVP)] and three presentations speeds [171, 250, and 305 wpm (words per minute)] on subjects' reading comprehension for different types of small screens for laptops, personal digital assistants (PDAs), and mobile phones. 12 college students who were native speakers of Chinese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Text display speed with the dynamic display type affected a user's visual performance in Wang and Kan's (2004) study. To determine the appropriate speed for scrolling text, Chen and Chien (2005) studied the effect of dynamic display and scrolling speed on reading Chinese text on a small screen. They suggested that a vertical continuous scrolling at a speed of 305 cpm should be used for Chinese characters on mobile phone screens.…”
Section: Correlation Among Sustained Attention Reading Comprehensionmentioning
confidence: 99%
“…Text display speed with the dynamic display type affected a user's visual performance in Wang and Kan's (2004) study. To determine the appropriate speed for scrolling text, Chen and Chien (2005) studied the effect of dynamic display and scrolling speed on reading Chinese text on a small screen. They suggested that a vertical continuous scrolling at a speed of 305 cpm should be used for Chinese characters on mobile phone screens.…”
Section: Correlation Among Sustained Attention Reading Comprehensionmentioning
confidence: 99%
“…Sandfeld and Jensen's (2005) [2] findings indicated that decreasing letter and target size impaired task performance; that is, participants did worse with small targets than they did with large ones in the same task. However, research by Chen and Chien (2005) [3] indicated that font and font size had no effect on reading efficiency. They found that how the information was displayed and the speed in which it was displayed affected comprehension of a given message.…”
Section: Introductionmentioning
confidence: 96%
“…A large volume of existing literature has explored the effects many factors can have on readability of small digital screens [6,7,8]. Some research has utilized scrolling text as a way to improve readability of in-vehicle displays [9].…”
Section: Introductionmentioning
confidence: 99%